Functional vision and cognition in infants with congenital disorders of the peripheral visual system. (25th April 2017) - Dale, Naomi; Sakkalou, Elena; O'Reilly, Michelle; Springall, Clare; De Haan, Michelle; Salt, Alison
Abstract : Aim: To investigate how vision relates to early development by studying vision and cognition in a national cohort of 1‐year‐old infants with congenital disorders of the peripheral visual system and visual impairment. Method: This was a cross‐sectional observational investigation of a nationally recruited cohort of infants with 'simple' and 'complex' congenital disorders of the peripheral visual system. Entry age was 8 to 16 months. Vision level (Near Detection Scale) and non‐verbal cognition (sensorimotor understanding, Reynell Zinkin Scales) were assessed. Parents completed demographic questionnaires. Results: Of 90 infants (49 males, 41 females; mean 13mo, standard deviation [SD] 2.5mo; range 7–17mo); 25 (28%) had profound visual impairment (light perception at best) and 65 (72%) had severe visual impairment (basic 'form' vision). The Near Detection Scale correlated significantly with sensorimotor understanding developmental quotients in the 'total', 'simple', and 'complex' groups (all p <0.001). Age and vision accounted for 48% of sensorimotor understanding variance. Infants with profound visual impairment, especially in the 'complex' group with congenital disorders of the peripheral visual system with known brain involvement, showed the greatest cognitive delay. Interpretation: Lack of vision is associated with delayed early‐object manipulative abilities and concepts; 'form' vision appeared to support early developmental advance. This paper provides baseline characteristics for cross‐sectional and longitudinal follow‐up investigations in progress. A methodological strength of the study was the representativeness of the cohort according to national epidemiological and population census data. What this paper adds: At 1 year, near‐detection vision is strongly associated with cognitive outcome. Infants with visual impairment have difficulty acquiring early manipulative abilities and object concepts, particularly if they have no vision. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. This article is commented on by Matsuba on page674 of this issue.